Potassium Channels and Human Epileptic Phenotypes: An Updated Overview - Villa, Chiara; Combi, Romina (Frontiers in Cellular Neuroscience, 2016)
Potassium (K+) channels are expressed in almost every cells and are ubiquitous in neuronal and glial cell membranes. These channels have been implicated in different disorders, in particular in epilepsy. K+ channel diversity depends on the presence in the human genome of a large number of genes either encoding pore-forming or accessory subunits. More than 80 genes encoding the K+ channels were cloned and they represent the largest group of ion channels regulating the electrical activity of cells in different tissues, including the brain. It is therefore not surprising that mutations in these genes lead to K+ channels dysfunctions linked to inherited epilepsy in humans and non-human model animals. This article reviews genetic and molecular progresses in exploring the pathogenesis of different human epilepsies, with special emphasis on the role of K+ channels in monogenic forms.